Does it Pay to Speak Welsh? Exploring the Economic Outcomes of Welsh Language Graduates - Davies, Rhys; Huxley, Katy; Poole, John (International Journal of Population Data Science, 2025)
Objectives There is a lack of recent evidence on the association between Welsh language ability and employment outcomes. This paper addresses this gap by simultaneously examining the interplay between Welsh language ability and patterns of migration among recent cohorts of Welsh graduates and how these in turn influence employment outcomes. Methods Based upon Higher Education Statistics Agency data, we examine the university locations of six cohorts of Welsh domiciled Year 11 pupils (covering the period 2013-2018) who choose to enter Higher Education (HE). Using data from the 2011 Census and records related to compulsory and post-compulsory education, the characteristics of HE students who remain in Wales are compared to those who leave. Data from the Destinations of Leavers from Higher Education (DHLE) survey is used to examine migratory patterns following HE, how Welsh language influences graduate migration and how these in turn relate to employment outcomes. Results The existence of a ‘brain drain’ of graduate labour from Wales has become a focus of debate. Any region’s ability to generate, retain and attract graduate workers is critically linked to the relative employment opportunities that are available compared to elsewhere. The analysis confirms that those students who speak Welsh are more likely to remain in Wales for the purpose of attending university. In the context of the relatively poor economic performance of Wales, those students who migrate from Wales exhibit improved economic outcomes. Additional analysis will examine whether the ability to speak Welsh has a positive impact upon employment outcomes and whether there is separate and additional effect of receiving tuition through the medium of Welsh among those who choose to study in Wales. Conclusion The analysis emphasises the link between economic and language policy, as described within the Welsh Government’s national strategy Prosperity for All: Good quality jobs (in) attractive places…to live…(are required) to provide people with a reason to remain or return to work and live in communities where the Welsh language thrives.